Stick Gymnastics Training to Improve Motor Skills - Nurcahyo, Andi; Nur Khasanah; Lestari, Diah Aryati Puji; Sulistyowati, Sulistyowati (Jurnal Pengabdian KOLABORATIF, 2025)
Stick exercise training is a form of community fitness intervention aimed at improving motor skills, particularly among adults. This community service activity was carried out in RW 06, Kalibanteng Kulon Village, involving 20 participants, mostly women. The method used was direct training through a participatory approach, beginning with problem identification, followed by a pre-test, stick exercise session, and post-test. The evaluation results showed a significant improvement in participants’ motor understanding and skills, with scores increasing from 52% in the pre-test to 82% in the post-test. The 30% increase indicates the effectiveness of training methods using simple equipment like sticks. This program not only provides physical benefits but also encourages active community participation in fun, accessible, and healthy activities. Stick exercise training has proven to be an appropriate educational and preventive medium for sustainably developing motor capacity within the community.